Rethinking the demarcation of Malachi 2:17-3:5 - S. D. Snyman (Acta Theologica)
Demarcating a unit remains important for the interpretation and understanding of the particular unit in a (Biblical) book. In the case of the book of Malachi, the majority of scholars adhere to the traditional demarcation of the fourth unit in the book of Malachi (2:17-3:5). Closer investigation reveals that the matter is not as settled as one might think. Other possibilities are also advocated by scholars. Some regard Mal. 2:17-3:12 as a unit. Another possibility is to regard Mal. 2:17 as a unit on its own followed by either Mal. 3:1-5 or 3:1-12 as a separate unit. A third possibility is to view Mal. 2:17-3:6 as a unit. This paper argues for yet another possibility stretching from Mal. 2:17-3:7a. Arguments for this delimitation are given and the impact this new possibility has on the exegesis and eventual meaning of both Mal. 2:17-3:7a and the following unit (Mal. 3:7b-12) is explored.